Ectopic Fibrous Dysplasia Presenting As a Well-Circumscribed Orbital Mass. Issue 2 (28th October 2022) - Lee, Tonya C.; Topilow, Nicole J.; Ting, Michelle A.; Estrella, Melanie; Liu, Catherine Y.; Korn, Bobby S.; Ferguson, Cole J.; Kikkawa, Don O.
Abstract : The authors present the case of a middle-aged woman with subacute progressive swelling of the OD associated with pain and severely limited duction in all gazes. MRI demonstrated a ~3 cm circumscribed mass in the extraconal space, which displaced and distorted the globe and impinged upon ocular adnexa. She underwent lateral orbitotomy with bone osteotomy to remove the mass, and subsequent histopathologic examination showed woven bone set within a fibrotic background, microscopic features of fibrous dysplasia. Fibrous dysplasia is characterized by abnormal scar-like bony proliferation, typically within a preexisting structure of the skeletal system. To the authors' knowledge, this represents the first example of fibrous dysplasia presenting as an orbital mass unconnected to the craniofacial skeleton. Abstract : The authors describe an unusual case of fibrous dysplasia presenting as a discrete, circumscribed orbital mass separate from the craniofacial skeleton.